The daughter of time - Tey, Josephine (Penguin Books, 2022)
Scotland Yard inspector Alan Grant, recovering from a broken leg, becomes fascinated with a contemporary portrait of Richard III that bears no resemblance to the Wicked Uncle of history. But does this noble face really belong to one of the world's most heinous villains? Or was he the victim of one of the most insidious plots in history? Grant determines to find out once and for all, with the help of the British Museum and an American scholar, what kind of man Richard III really was and who killed the Princes in the Tower